(untitled) (La U Investiga, 2020)
Biosecurity standards are guidelines that reduce the risk of infection for both health care personnel and patients. However, the application of biosecurity standards has now been compromised by internal or external factors such as the lack of necessary supplies and the lack of knowledge on the part of professionals to attend to cases of patients with Covid-19, This research aims to analyse the application of biosecurity standards in nursing staff in times of pandemics at the Pelileo Basic Hospital in 2020. To this end, descriptive research with a quantitative approach was carried out, considering 85 nursing professionals as the target population, to whom a data collection instrument called Biosecurity Measures in Intra-Hospital Prevention was applied, which was adapted to the context of this research. As a result of the determination of a lack of knowledge about biosecurity in 15% of the population studied, it was also determined that there is not a 100% supply of necessary biosecurity supplies for nurses. Therefore, it has been concluded that training is essential for health professionals to meet biosecurity standards within their areas. In addition, each institution must provide the necessary equipment so that professionals can cope with the conditions of the current pandemic and not put their health at risk.